2014
DOI: 10.1111/epi.12580
|View full text |Cite
|
Sign up to set email alerts
|

Altered thalamocortical functional connectivity in idiopathic generalized epilepsy

Abstract: SUMMARYObjective: Aberrant thalamocortical network has been hypothesized to play a crucial role in the fundamental pathogenesis underlying idiopathic generalized epilepsy (IGE). We aimed to investigate alterations of thalamocortical functional network in patients with IGE using thalamic seed-based functional connectivity (FC) analysis, and their relationships with frontal cognitive functions and clinical characteristics. Methods: Forty-nine IGE patients (31 with juvenile myoclonic epilepsy, 17 with IGE with ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
86
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 40 publications
16
86
4
1
Order By: Relevance
“…However, another study found a different pattern of connectivity by using a similar analytic strategy. 21 This inconsistency is at least partly due to the different locations of seed regions in these studies. To avoid the bias of a predefined seed region in the present study, we performed a voxelwise functional connectivity analysis (expressed as FCS) between the thalamus and cortex.…”
Section: Discussionmentioning
confidence: 87%
“…However, another study found a different pattern of connectivity by using a similar analytic strategy. 21 This inconsistency is at least partly due to the different locations of seed regions in these studies. To avoid the bias of a predefined seed region in the present study, we performed a voxelwise functional connectivity analysis (expressed as FCS) between the thalamus and cortex.…”
Section: Discussionmentioning
confidence: 87%
“…For example, patients with generalized tonic–clonic seizures only (GTCSO) revealed reduced gray matter in the ventral anterior and lateral nuclei of the thalamus compared to healthy controls 3, 23, 24. In a group of patients with juvenile myoclonic epilepsy (JME), shape analysis showed surface reduction in the medial and lateral nuclei of bilateral thalami25 and decreased gray matter volume in the anteromedial thalamus has also been found in patients with JME11 and in a group of mixed GGE patients 26. Similarly, gray matter volume reduction in bilateral thalami has been reported in patients with CAE 9.…”
Section: Discussionmentioning
confidence: 97%
“…To date, the majority of previous studies have predominately detected abnormal epileptic at a conventional lowfrequency range (0.01-0.08 Hz) because the lowfrequency range was thought to be linked to neuronal intrinsic fluctuations, which may ignore some meaningful information associated with frequencyspecific spontaneous blood oxygen level-dependent (BOLD) fluctuation [5][6][7][8] . Besides, neighboring frequency bands within the same neuronal network may compete or interact with each other, which means that the brain intrinsic resting-state functional networks are frequency-dependent 9,10 .…”
Section: Introductionmentioning
confidence: 99%